Relationship Between Maternal Parity and Primary Postpartum Hemorrhage - Evie Ludviyah; Sri Wahyuningsih; Agustina Widayati; Sunanto (Health and Technology Journal (HTechJ), 2023)
Primary postpartum hemorrhage is bleeding that occurs within the first 24 hours. Primary postpartum hemorrhage greatly affects maternal parity. One of the causes of maternal death related to bleeding is maternal parity. This study aims to determine the relationship between maternal parity and primary postpartum hemorrhage. This research is an analytic observational study, while the research design is retrospective. Data were taken from medical records that entered the obstetrics and gynecology department of Bhayangkara Lumajang Hospital from January to April 2022 with a population of 160 spontaneous postpartum mothers. The sample studied was 40 respondents and was taken using Simple Random Sampling. Bleeding cases at Bhayangkara Lumajang Hospital from January to April 2022 showed a parity of respondents who were at risk of experiencing primary postpartum hemorrhage as much as (40%), parity at risk of not experiencing primary postpartum hemorrhage as much as (17.5%), the results obtained were X² greater from p so it can be concluded that there is a relationship between maternal parity and primary postpartum hemorrhage. It is hoped that health workers in the delivery room will refresh their knowledge to increase their knowledge and services so that complications and complications do not occur in childbirth.